Kesadaran Perpajakan dan Sosialisasi Perpajakan terhadap Kepatuhan Wajib Pajak Pelaku UMKM (Sebuah Studi Literatur) - Jalilut Jabar (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
The literature review article on Tax Awareness and Tax Dissemination of Taxpayer Compliance with MSME Actors (A Literature Study) is an academic paper. The aim is to formulate a research hypothesis about the influence between variables, which can be used for further research. How to write this literature review article: Using library research methods sourced from online media such as Google Scholar, Mendeley, and other online scientific media. The results of this literature review article 1. Tax awareness influences MSME tax compliance; 2. Tax socialization affects MSME tax compliance.